2006
DOI: 10.3109/s10165-006-0479-1
|View full text |Cite
|
Sign up to set email alerts
|

A case of systemic sclerosis complicated by idiopathic portal hypertension: case report and literature review

Abstract: We encountered a 62-year-old woman who had systemic sclerosis (SSc) complicated by idiopathic portal hypertension (IPH). She had a 10-year history of scleroderma and Raynaud's phenomenon. She also had pancytopenia, splenomegaly, and esophageal varices. Treatment with prednisolone and endoscopic variceal ligation resulted in improvement of her symptoms. According to our literature review, the prognosis of patients with SSc complicated by IPH is relatively poor. However, the factors that predict outcome of these… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 7 publications
0
8
0
Order By: Relevance
“…However, it is widely accepted that autoimmune diseases (especially connective tissue diseases) increases the prevalence of IPH in certain patient groups. The most important IPH associated diseases are mixed connective tissue disease (6 cases [6] ), systemic sclerosis (20 cases [7] ) and systemic lupus erythematosus (16 cases [8] ). In addition, a Japanese survey [9] found that hypergammaglobulinemia is the most common presenting autoimmune dysfunction (26% of all included IPH patients), along with chronic thyroiditis as the most common autoimmune disease.…”
Section: Autoimmunity Theorymentioning
confidence: 99%
“…However, it is widely accepted that autoimmune diseases (especially connective tissue diseases) increases the prevalence of IPH in certain patient groups. The most important IPH associated diseases are mixed connective tissue disease (6 cases [6] ), systemic sclerosis (20 cases [7] ) and systemic lupus erythematosus (16 cases [8] ). In addition, a Japanese survey [9] found that hypergammaglobulinemia is the most common presenting autoimmune dysfunction (26% of all included IPH patients), along with chronic thyroiditis as the most common autoimmune disease.…”
Section: Autoimmunity Theorymentioning
confidence: 99%
“…Recent studies have shown that IPH is associated with many autoimmune diseases, such as systemic sclerosis 15 , systemic lupus erythaematosus 16 and rheumatoid arthritis 9 . These results, combined with our own, indicate that IPH may be secondary to inflammation of connective tissue and vasculitis.…”
Section: Discussionmentioning
confidence: 99%
“…In some patients we can find HPS in association with immunological disorders such as immunodeficiency [8], rheumatoid arthritis, systemic lupus erythematosus, scleroderma, celiac disease, Sjögren's Syndrome (SS) [9]. Very few examples of association between HPS and Systemic Sclerosis (SSc) are described in the literature: In 2005 Kogawa et al 10] presented a rare case of a 72 years-old Japanese woman with HPS associated with SSc and SS; and in 2006 Takagi et al report a similar case with portal hypertension and SSc [11]. In 2014 the case of a female patient with atypical hepatic changes due to HPS with limited systemic sclerosis was referred in Brazil [12].…”
Section: Abstract: Idiopathic Non-cirrhotic Portal Hypertension (Incph;mentioning
confidence: 99%